Створення алгоритму управління камерами-павуками для телетрансляції різних подій (частина 1) - Солодов, В. Д. (ХНУРЕ, 2021)
In this paper, we will consider a method of improving the use of so-called spider chambers flying over the stadium on special suspension cables. Such technologies came from Hollywood, and now they are used in the shooting of almost all high-budget films
Keywords: камера-павук; алгоритм управління